Targeting Tumor Perfusion and Oxygenation to Improve the Outcome of Anticancer Therapy1 - Jordan, Benedicte F.; Sonveaux, Pierre (Frontiers in Pharmacology, 2012)
Radiotherapy and chemotherapy are widespread clinical modalities for cancer treatment. Among other biological influences, hypoxia is a main factor limiting the efficacy of radiotherapy, primarily because oxygen is involved in the stabilization of the DNA damage caused by ionizing radiations. Radiobiological hypoxia is found in regions of rodent and human tumors with a tissue oxygenation level below 10 mm Hg at which tumor cells become increasingly resistant to radiation damage. Since hypoxic tumor cells remain clonogenic, their resistance to the treatment strongly influences the therapeutic outcome of radiotherapy. There is therefore an urgent need to identify adjuvant treatment modalities aimed to increase tumor pO2 at the time of radiotherapy. Since tumor hypoxia fundamentally results from an imbalance between oxygen delivery by poorly efficient blood vessels and oxygen consumption by tumor cells with high metabolic activities, two promising approaches are those targeting vascular reactivity and tumor cell respiration. This review summarizes the current knowledge about the development and use of tumor-selective vasodilators, inhibitors of tumor cell respiration, and drugs and treatments combining both activities in the context of tumor sensitization to X-ray radiotherapy. Tumor-selective vasodilation may also be used to improve the delivery of circulating anticancer agents to tumors. Imaging tumor perfusion and oxygenation is of importance not only for the development and validation of such combination treatments, but also to determine which patients could benefit from the therapy. Numerous techniques have been developed in the preclinical setting. Hence, this review also briefly describes both magnetic resonance and non-magnetic resonance in vivo methods and compares them in terms of sensitivity, quantitative or semi-quantitative properties, temporal and spatial resolutions, as well as translational aspects.